THE STATE OF RUSSIAN OPPOSITION IN TIMES OF WAR IN UKRAINE - Szeląg, Paulina; Wasiuta, Olga (Torun International Studies, 2024)
The main aim of the article is to analyse the concept of the Russian opposition before and after the outbreak of the war in Ukraine. We establish how and why the Russian opposition has been changing in the last decades. The article is divided into three parts. In the first part a phenomenon of the Russian opposition is showed. The second part is the analysis of the evolution of the Russian opposition since 1990s. The third part presents the composition of the Russian opposition in 2022 and its reaction to the war in Ukraine. We hypothesize that Putin’s regime has been constantly combating and weakening the opposition in Russia in recent years. As a result, in modern Russia the systemic opposition is no longer existent and the non-systemic one is fragmented, chaotic and almost entirely outside the Russian Federation. What is more, the outbreak of the war in Ukraine, has no impact on strengthening the Russian opposition and creating cooperation between its main factions and the oppositionists do not speak with one voice. The article consists of the diagnosis of the contemporary Russian opposition, showing its structure and pointing out its weaknesses. The article is based on desk research, historical method, institutional approach, and comparative analysis.